Molecular Identification of Burkholderia Cepacia Complex and Species Distribution Among Cystic Fibrosis Patients Seen at the Reference Center in Southern Brazil - Leite, Fernanda Concli; Pinheiro Machado, Alice Beatriz Mombach; Lutz, Larissa; Vieira, Maria Izolete; Barth, Afonso Luis (Clinical and Biomedical Research, 2011)
Background: Burkholderia cepacia complex (Bcc) infections in cystic fibrosis (CF) patients are associated with decline in lung function and reduced survival. The potential transmissibility of Bcc among CF patients has been reported, indicating that strict segregation of CF patients with Bcc is crucial. Aims: To standardize the PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) assay in order to identify Bcc species and to establish the prevalence of Bcc species and their susceptibility profile among CF patients seen at the Hospital de Clínicas de Porto Alegre (HCPA). Methods: The classification of the clinical isolates recovered from respiratory tract specimens of CF patients as Bcc was achieved using the API-20NE® phenotypic commercial system. The identification of the Bcc species was performed using PCR-RFLP. The antimicrobial disk diffusion susceptibility testing was performed according to the CLSI (2006). Results: API-20NE® was able to identify Bcc isolates (244 specimens), such as B. cepacia, indicating that it was not able to distinguish among the Bcc species. The PCR-RFLP molecular method discriminated the eight reference Bcc species, thus validating the method for clinical isolates. Bcc prevalence determined by PCR-RFLP was 10.6% (26/244). The molecular analysis identified B. cenocepacia in 53.8% (14/26) of infected patients, B. multivorans in 15.4% (4/26), and B. vietnamiensis and B. ambifaria in 7.7% (2/26). The antibiotic resistance profile was variable among Bcc species. Conclusions: The PCR-RFLP method was validated for the identification of Bcc species. B. cenocepacia proved to be the most prevalent species among the CF patients seen at the HCPA.